2023
DOI: 10.1049/tje2.12229
|View full text |Cite
|
Sign up to set email alerts
|

Modelling, simulation and performance comparison of different membership functions based fuzzy logic control for an active magnetic bearing system

Abstract: In-house prototype model of an active magnetic bearing is built and using its physical parameter values a linearized transfer function of order two, is mathematically obtained for a specific point of operation. In this work, a closed loop active magnetic bearing system is proposed and controller for this closed loop is designed using fuzzy logic control. Two different fuzzy inference systems: Mamdani and Sugeno fuzzy inference system constructed individually with eleven different types of membership functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Similar comparative studies were conducted in various fields, such as optical [19] and wireless [20] networks, magnetic bearing system control [21], chaotic time series prediction [22], evaluation of user experience for specific applications [23], and streamflow prediction in the hydrological field [24]. Although Takagi-Sugeno usually showed better results, the research in the hydrological domain showed that the Mamdani FIS is more suitable.…”
Section: Literature Reviewmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar comparative studies were conducted in various fields, such as optical [19] and wireless [20] networks, magnetic bearing system control [21], chaotic time series prediction [22], evaluation of user experience for specific applications [23], and streamflow prediction in the hydrological field [24]. Although Takagi-Sugeno usually showed better results, the research in the hydrological domain showed that the Mamdani FIS is more suitable.…”
Section: Literature Reviewmentioning
confidence: 70%
“…Fuzzification is responsible for converting the numerical input values (i.e., the observed relative velocity RELATIVE_VELOCITY and the spacing I NTERVEH ICLE_SPACI NG between the LV and FV at time t − τ) into linguistic variables. The names chosen for the linguistic variables are similar to those existing in other similar studies [21,27,39,40], such as negative big (NB), negative small (NS), zero (ZE), positive small (PS), and positive big (PB). The knowledge base contains the rules expressed as "IF THEN" conditions that define the logical relations between the inputs RELATIVE_VELOCITY and I NTERVEH ICLE_SPACI NG and the output s_OFFSET_x, where x = {M; TS} is defined separately for Mamdani (Section 3.2.2) and Takagi-Sugeno FISs (Section 3.2.3).…”
Section: Fuzzy-based Calibration Of Continuous-time Car-following Modelsmentioning
confidence: 99%
“…A membership function is a function that can work in mapping points in the input data to their membership values. Membership functions that are generally used and have advantages in representing and have broader capabilities in forming various forms of distribution are Gaussian and Generalized Bell membership functions (Gupta et al, 2023).…”
Section: Data Pre-processingmentioning
confidence: 99%
“…The mapping between 0 and 1 for each data point in the input space is determined by a membership function in the form of a fuzzy curve [85]. Membership in fuzzy sets has different shapes consisting of linear, bell, gaussian, trapezoidal, shoulder curves (left and right), and triangular shapes [103], [104]. In this study, only two types of curves were used, namely the shoulder curve (left and right) and the triangle curve.…”
Section: Fuzzy Logicmentioning
confidence: 99%